Penerapan Reward dan Punishment dalam Pembelajaran Al-Qur’an Metode Ummi di SDIT Al Firdaus Banjarmasin - Muhammad Iqbal Ansari; Sari Kumala; Ice Tamala (IAI Al Khoziny Buduran Sidoarjo, 2023)
This study aims to describe the application of reward and punishment in learning to recite the ummi method at SDIT Al Firdaus Banjarmasin and to describe the supporting and inhibiting factors for implementing reward and punishment in learning to recite the ummi method at SDIT Al. Banjarmasin Firdaus. This study uses a qualitative approach with a case study type of research. Data collection is done through observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion. Researchers used technique triangulation and source tirangulation to obtain data validity. Based on the research results, it can be obtained in the form of reward and punishment in learning the Qur'an with the Ummi method at SDIT Al Firdaus Banjarmasin. Forms of reward include: 1). Quarterly Monthly Snack Rewards, 2). Ummi Volume Increase Figure Rewards, 3). Praise Award, 4). Star Award/Value, 5). Food Rewards from Al-Qur'an Teachers, 6). Treat Gifts. While the forms of punishment include: 1). Standing in place, 2). Reprimand, 3). Suggestion, 4). Saying Istighfar, 5). Clean up trash in class/field, 6). Time out / leave the group. Factors supporting the application of reward and punishment in learning the Ummi Qur'an method at SDIT Al Firdaus Banjarmasin are: 1). Teacher creativity, 2). Enthusiastic students, 3). Training and Budget. The inhibiting factors are: 1). Teachers are still shy, 2). Students are not hindered, 3). Training is rarely held.